Cash Waqf Investment Models in Indonesia (UIN Sunan Kudus, 2023)
In Indonesia, Cash Waqf investments are IDR 1.4 trillion, showing the strong potential of the financial instrument. However, alternative investment models are needed to obtain optimal results. The models support strategic programs in various sectors, including education, health, economy, humanity, and da'wah. Therefore, this research aimed to identify Cash Waqf investment models using a qualitative method with a literature study approach. The literature review adopts the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) model. The results show that there are 10 Cash Waqf investment models implemented in Indonesia, namely (1) Micro, Small and Medium Enterprises (MSME) Financing, (2) Cash Waqf Linked Sukuk, (3) Islamic Social Entrepreneurship, (4) Education Management and Operations, (5) General Credit Loans, (6) Sharia Bank Cooperation, (7) Land Waqf Development, (8) Stock Waqf, (9) Hospitals, and (10) Waqf Bank. The government and Nadzir Waqf need to respond to the results by selecting a form of Cash Waqf investment with the highest value.